FACTORS CAUSING POVERTY AND MECHANISMS OF THEIR REDUCTION - Asqaraliyev Saidali Rahmonaliyevich (American Journals, 2023)
The mechanism of poverty formation is a complex and dynamic process. Currently, there is no complete theory of research on the factors that form poverty. This article examines the theoretical aspects of poverty-causing factors. Today, various factors causing poverty are analyzed: economic factors, individual factors, social factors, geographical factors, etc.
Keywords: Poverty, development, human capital, socio-economic factors, well-being, scientific competence.